2017
DOI: 10.1111/cbdd.13049
|View full text |Cite
|
Sign up to set email alerts
|

Antilipase and antiproliferative activities of novel fluoroquinolones and triazolofluoroquinolones

Abstract: Fluoroquinolones (FQs) have been identified recently as potent inhibitors of pancreatic lipase (PL). The aim of this study was to synthesize novel FQs and triazolofluoroquinolones (TFQs) and to evaluate them in vitro with respect to their antilipolytic efficacy and potency properties. The PL-IC values of 12 FQs and TFQs (3 (a-c)-6 (a-c)) were in the range of 12.5-189.1 μm. These values are further supported by docking studies. The suggested association between obesity and colorectal cancer initiated the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The position of hydroxyl groups in the ring affects lipase inhibition; 2‐hydroxy benzoic acid or benzoyl derivatives were reported with best inhibitory activity and this possibly related to increased phenolic group acidity for such compounds through intra‐molecular H‐Bs of close ortho groups (Buchholz & Melzig, and references cited therein). Similar to our findings with FQs research, Arabiyat () and Arabiyat et al (, ) reported that 2‐hydroxy benzoic acid compounds replaced with a methoxy group are weak inhibitors of PL and the inhibitory effects of hydroxyl groups in the ortho ‐position were stronger than at the para ‐position (Buchholz & Melzig, ; Menteşe et al, ). It is concluded that loosing free acidic OH or COOH can lessen the activity and this can be explained through the loss of the intra‐molecular H‐B for both ortho related keto or carboxyl groups with hydroxyl group at position 2.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…The position of hydroxyl groups in the ring affects lipase inhibition; 2‐hydroxy benzoic acid or benzoyl derivatives were reported with best inhibitory activity and this possibly related to increased phenolic group acidity for such compounds through intra‐molecular H‐Bs of close ortho groups (Buchholz & Melzig, and references cited therein). Similar to our findings with FQs research, Arabiyat () and Arabiyat et al (, ) reported that 2‐hydroxy benzoic acid compounds replaced with a methoxy group are weak inhibitors of PL and the inhibitory effects of hydroxyl groups in the ortho ‐position were stronger than at the para ‐position (Buchholz & Melzig, ; Menteşe et al, ). It is concluded that loosing free acidic OH or COOH can lessen the activity and this can be explained through the loss of the intra‐molecular H‐B for both ortho related keto or carboxyl groups with hydroxyl group at position 2.…”
Section: Introductionsupporting
confidence: 92%
“…Previous work by our group on FQs has shed some light on the main SAR features of PL inhibitors derived from FQs. We can conclude at this stage that the basic requirements for a highly active antipancreatic lipase FQ derivative are as seen in Chart (Arabiyat, ; Arabiyat et al, , ): Free 4‐oxo‐pyridine‐3‐carboxylic acid is seen as esterification of COOH group led to very weak activity. Free rotating hydrogen bond groups at C‐7 and C‐8 are essential and major requirements for activity. Lipophilicity was a major feature in all active FQs, and the c log P was above 3. The rigid structure of FQs between C7‐8 decreases PL inhibitory activity. A lipophilic phenyl group substituted at C‐7 carrying methoxy or amine, such as anisidine and aniline substituents, was the most active through their capability of forming extra H‐Bs. …”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations